Assessment of Dual-Gate AlGaN/GaN MISHEMT for high temperature DC to DC converter. (August 2020) - Singh, Preeti; Kumari, Vandana; Saxena, Manoj; Gupta, Mridula
Abstract: Numerical assessment of Dual-Gate AlGaN/GaN MISHEMT have been presented in this paper. Analytical model has been developed and the various parameters extracted are surface potential, electric field and threshold voltage for different device specifications. Threshold voltage of nearly 0.15 V has been computed which is nearly same to that of simulated Dual-Gate MISHEMT. Simulations have been performed using ATLAS TCAD tool. Dual-Gate MISHEMT with different gate dielectric materials such as Si3 N4 and gate stack combinations like HfO2 /Al2 O3 has been analyzed. From the results it has been inferred that at higher temperature, drain current and transconductance reduces due to lower electron sheet concentration. Different combinations of gate biases (applied at the second gate i.e. Gate 2 presented near the drain side) has been used for optimizing the device parameter for better switching performance. For DG-MISHEMT with barrier thickness of 22 nm (both the gates connected together), ION /IOFF ratio reduces from 10 9 to 10 6 for high temperature (upto 423 K) due to reduced sheet carrier concentration. For inductance load, output drain voltage exhibits voltage range of 9.2V/2.3V for gate pulse of -8V/+2V with 30% duty cycle. Also, it is seen that as barrier thickness is varied from 18 nm to 30 nm, IOFF increases and results in reduced output drain voltages. Performance of Single Gate and Double Gate MISHEMTs has also been compared for DC-to DC converter using inductance load circuit. Highlights: Analytical model for Dual-Gate AlGaN/GaN MISHEMT. Temperature based investigation upto 500K for Dual-Gate AlGaN/GaN MISHEMT. Effect of barrier thickness on the ION /IOFF ratio has been investigated. DC-to-DC converter using Dual-Gate AlGaN/GaN MISHEMT and inductor load.